Determination of effective properties of piezoelectric composites containing short fibers - Singh S.K.; Panda S.K. (My University, 2025)
The present paper studies the effects of local field fluctuations on the effective electromechanical coupling coefficients of piezoelectric composites containing short fibers. The finite-element method (FEM) is applied to study the overall behavior of such composites. Geometric models containing spheroid inclusions of two fiber arrangements, simple cubic and body-centered cubic, are modeled with FEM to predict the effective coefficients. The results thus obtained are validated with the results obtained from the analytical method based on Eshelby's solution to the ellipsoidal inclusion problem. The analytical solution obtained through the Eshelby method is generalized for spheroid inclusions to compare the results with those of the FEM study. All finite-element studies are carried out through the finite-element software package Ansys 18.0. A detailed analysis of results is presented to understand better the behavior of such composites and their effective property variation with change in fiber volume fraction. © 2020 ICE Publishing: All rights reserved.